Effects of exercise programs on phase angle in older adults: a systematic review and meta-analysis - Martins, Alexandre Duarte (2022)
The purpose of this study was to calculate the effects of exercise programs on phase angle (PhA) in older people. A systematic review was undertaken in multiple electronic databases in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses statement guidelines for the purposes of selecting randomized controlled trials that measured the effects of the exercise programs on PhA in older adults on 31 March 2022. We carried out a random-effect meta-analysis for the effects of exercise programs on PhA. Additionally, we analysed the differences between subgroups in terms of weekly frequency, number of sets and repetitions, and duration of interventions. Studies were methodological assessed through the PEDro scale where one had excellent, ten had good, and three had poor methodological quality. For the purposes of the study, fourteen studies met the criteria for in clusion. However, four studies did not have enough information to be included in the quantitative analysis. The remaining ten articles revealed moderate effects on PhA in favour of intervention groups (p=0.009, SMD=0.72 [0.46–0.99], I 2 =54%). The meta-analysis also showed that interventions lasting twelve weeks are more suc cessful in generating positive effects on PhA as opposed to eight weeks (SMD’s=0.79 vs. 0.64, respectively). These results indicate that resistance training (RT) is an effective and safe to improve PhA in the older people, especially through RT programs lasting from eight to twelve weeks. A novel finding of this study was that RT is the most used type of exercise by authors when assessing the PhA in older adults.